2018
DOI: 10.1021/acssuschemeng.8b01397
|View full text |Cite
|
Sign up to set email alerts
|

Mussel Adhesive-Inspired Design of Superhydrophobic Nanofibrillated Cellulose Aerogels for Oil/Water Separation

Abstract: Inspiration from biomimeticsthe chemistry of mussel adhesiveswas taken for imparting superhydrophobic properties to nanofibrillated cellulose (NFC) matrices. A polydopamine (PDA) surface coating was introduced, acting as an anchor between the NFC scaffold and octadecylamine (ODA): PDA is coated onto the NFC scaffolds by its adhesive properties and the ODA is successfully attached to the PDA by a Schiff base reaction. The ultralow density of 6.04 mg/cm3 combined with the high contact angle of 152.5° endows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(54 citation statements)
references
References 45 publications
(75 reference statements)
0
54
0
Order By: Relevance
“…The specific surface area and mesopore size distribution of wood aerogel were characterized by the nitrogen adsorption-desorption isotherms and the Barrett-Joyner-Halenda (BJH) method, as shown in Figure 4. The wood aerogel exhibited type IV adsorption isotherms and possessed a type H3 hysteresis loop in Figure 4a [32,33]. The latter demonstrated the presence of a mesoporous structure in the wood aerogel.…”
Section: Specific Surface Area and Pore Size Distribution Analysismentioning
confidence: 95%
“…The specific surface area and mesopore size distribution of wood aerogel were characterized by the nitrogen adsorption-desorption isotherms and the Barrett-Joyner-Halenda (BJH) method, as shown in Figure 4. The wood aerogel exhibited type IV adsorption isotherms and possessed a type H3 hysteresis loop in Figure 4a [32,33]. The latter demonstrated the presence of a mesoporous structure in the wood aerogel.…”
Section: Specific Surface Area and Pore Size Distribution Analysismentioning
confidence: 95%
“…An alternative strategy is to modify the NFC dispersions prior to the freeze or supercritical drying process. [108][109][110][111][112] In this way, the entire cellulose aerogel could be functionalized. For instance, Zhang et al 108 reported a facile process to prepare hydrophobic, exible, and low-density (#17.3 mg cm À3 ) cellulose aerogels by freeze-drying aqueous NFC suspensions with methyltrimethoxysilane (MTMS) as a silylating agent.…”
Section: Cellulose Nanomaterials and Wood For Oil/water Separation Anmentioning
confidence: 99%
“…The hydrophobic sponges maintained their shape and oil absorption capacity aer cyclic extraction/absorption, demonstrating their reusability. Inspired by the chemistry of mussel adhesives, Gao et al 109 developed a facile and novel method to fabricate low-density (6.04 mg cm À3 ), superhydrophobic NFC aerogels by dipping NFCs into a dopamine/octadecylamine (ODA) emulsion, followed by freeze-drying. Here, polydopamine (PDA) was coated onto the NFC by its adhesive properties and the ODA was then attached to the PDA by a Schiff base reaction (Fig.…”
Section: Cellulose Nanomaterials and Wood For Oil/water Separation Anmentioning
confidence: 99%
“…Asha et al ., for example, used dopamine to prepare zwitterionic coating materials with good antifouling and antimicrobial properties via Michael‐type additions and Schiff base reactions with amino group‐rich polyethylenimine . However, the high cost and general scarcity of dopamine as a raw material significantly impede its practical application …”
Section: Introductionmentioning
confidence: 99%
“…28,29 However, the high cost and general scarcity of dopamine as a raw material significantly impede its practical application. 30,31 Low-cost dopamine analogues have also garnered significant research interest to this effect. Tannic acid is a natural polyphenol that is low-cost, environmentally friendly, readily available, and generally biocompatible.…”
Section: Introductionmentioning
confidence: 99%